KAPOSI SARCOMA IN AN IMMUNOSUPPRESSED PATIENT WITH PRESUMED CROHN'S DISEASE: IATROGENIC OR EPIDEMIC?. (21st January 2021) - Claytor, Jennifer; Viramontes, Omar; Conner, Stephanie; Wen, Kwun Wah; Beck, Kendall
Abstract: Introduction: Biologic immunosuppression and HIV infection both carry risks of infection and malignancy. Small series suggest that patients living with well-controlled HIV may safely and efficaciously use biologics, like TNF-alpha inhibitors (TNF-I). However, no current U.S. guidelines exist to screen for HIV infection among high-risk groups prior to starting TNF-I. We describe the case of a patient who received TNF-I for Crohn's Disease without any HIV testing, who developed potentially avoidable extensive Kaposi Sarcoma. Case Description: A healthy 32-year-old man presented with 1 month of diarrhea and a 15-lb weight loss. Fecal calprotectin, ESR, and CRP were markedly elevated. Endoscopy demonstrated severe rectal inflammation with perirectal abscess and perianal skin tags, suggestive of inflammatory bowel disease. Biopsies showed active colitis with ulceration, cryptitis, and fibropurulent debris without evidence of granulomata, dysplasia, or CMV. He was treated with IV antibiotics, IV steroids, and 2 infusions of infliximab at 5 mg/kg. He continued to have 4 loose stools an hour, limiting his steroid wean. One month later, he developed painful, violaceous plaques on his face, buccal mucosa, torso, and lower extremities. Biopsy showed Kaposi Sarcoma, and HIV test was positive, with viral load 3292 and CD4 count 248. Although in a monogamous relationship with his husband, a well-recognized risk factor for HIV acquisition, he had never been tested for HIV. Antiretroviral therapy was initiated promptly. Repeat rectal biopsies stained positive for HHV-8 and CMV, concerning for rectal KS and CMV proctitis. He started valgancyclovir but self-increased prednisone, with poor symptom relief. Review of the initial endoscopy confirmed no obvious HHV-8 positivity. Three weeks after HIV diagnosis, he developed new red nodules across his chest, suspicious for worsening KS due to immune reconstitution inflammatory syndrome (IRIS). He completed 12 cycles of chemotherapy and had no sign of residual IBD on recent colonoscopy. KS is his presumed original diagnosis. Discussion: Current U.S. guidelines do not recommend HIV screening prior to TNF-I use, despite the heightened risks of cumulative immune dysregulation. Our patient should have been screened annually for HIV according to CDC guidelines. Further, his uncontrolled HIV infection in combination with TNF-I and high dose steroids led to life-threatening Stage IV malignancy (KS), complicated by immune reconstitution inflammatory syndrome and poor ART absorption. We propose that all patients should be screened for common risk factors for HIV acquisition, such as men who have sex with men or intravenous drug use. For high risk patients, gastroenterologists should consider screening for HIV, in addition to tuberculosis and hepatitis, prior to immunosuppression with TNF-I.